At a crossroads of cancer risk and aging: the role of telomeres - Gerashchenko, B.I. (Experimental Oncology, 2010)
The risk of overall cancer inevitably increases with advancing age. The cancer incidence rate is not constant within the human life span (it exponentially increases with advancing age). Aging itself is a complex biological process with a poorly understood mechanism of its regulation. The aging process, as evidenced from the survey of the chances for death for the large cohort of people of various age groups, manifests probably due to a progressive accumulation of diverse adverse changes that increase the risk of death. While an increase of cancer risk due to aging cannot be fully explained, the length of telomeres (biomarker of aging) appears to be important to predict this risk. Cellular senescence, which is believed to be associated with dysfunctional (shortened) telomeres, may contribute to the aging of a whole organism. Here, based on recent literature data, we investigate the possible link between telomere dysfunction associated cellular senescence and tumorigenesis.